An investigation of the feasibility of vaccinating against the Old World Screwworm fly Chrysomya bezziana - Peter Willadseni; Sujitno Partoutomo (Indonesian Center for Animal Research and Development (ICARD), 2000)
The problem of the Old World Screwworm fly Chrysomya bezziana and the limitations of current methods of control are discussed briefly. Any attempt to investigate the feasibility of vaccinating against the fly, as a novel control technology, demands the establishment of methods for fly culture, the production of sources of antigens and the development of assay techniques suitable for the assessment of vaccination effects. This must be coupled to a strategy for vaccine development. This strategy is described, as a prelude to a series of papers evaluating the feasibility of vaccination in detail. Key words: Chrysomya bezziana, screwworm fly, vaccine